A study on inappropriate attendance to Emergency Department Hospital Universiti Sains Malaysia - Wahab, Nora (2018)
Introduction This study aimed to determine the prevalence of inappropriate attendance to Emergency Department in Hospital Universiti Sains Malaysia (USM) within November 2016 to January 2017, demographic data, percentage of attendance for 24 hours and days in a week, percentage of common diagnosis for inappropriate visit. This study also aimed to identify the associated factors of inappropriate attendance to Emergency Department Hospital Universiti Sains Malaysia Methodology This cross sectional study was performed in the emergency department of Hospital Universiti Sains Malaysia, Kubang Kerian, and Kelantan. By using systematic random sampling, a sample of 346 cases was selected. The appropriateness of the attendance then further evaluated base on validated decision flow chart. The association between socio-demographic and inappropriate visit to Emergency department was analysed. Result The total sample reviewed for this study was 346 cases. Men and women were equally represented.95% was Malay and the rest is non-Malay (5%). Of the total number of visit to the A&E, 22.8% (95%CI 0.18 to 0.27) were evaluated as inappropriate and remaining as appropriate. The 24 hours utilization pattern showed the highest peak of utilization of A&E was at 2200-2359 hour ( 95 cases) and the highest peak for inappropriate use also was at 2200-2359 hour (25 cases).The highest rate for inappropriate attendance to Emergency Department was on Friday ( 25.3%) . Type of illness contributed for inappropriate visit were Upper Respiratory Tract Infection (40%) ,mild acute gastroenteritis (3.5%),musculoskeletal pain (1.6%),soft tissue injury (2%) urinary tract infection (0.6%),scabies (0.6%),eczema (0.3%),varicella zoster (0,3%),conjunctivitis (0.3%),request medication (0.3%), simple abscess (0.3%), and constipation colic(0.3%). Factors associated with inappropriate visits were group of >45 years old (p <0.05), race (p=0.949), gender (p=0.749) and type of illness (p=0.997). Conclusion Inappropriate attendance to emergency department HUSM is still significant .Although certain group of user was recognised as contributor for inappropriate attendance, others factors still have to recognise and evaluate so that proper steps and policies can be taken for a better health services. .